3,5-dinitrobenzamidas e 3,5-dinitrobenzoatos sintéticos: avaliação antifúngica e desenvolvimento de uma nanoemulsão - Duarte, Allana Brunna Sucupira (2023)
Infections caused by fungi are among the most frequent public health problems affecting mainly immunocompromised patients. Currently, there is a restricted number of antifungals and the resistance of microorganisms to these drugs compromises the effectiveness of the treatment. Thus, the search for synthetic antimicrobial compounds increased due to their key role in the development of new drugs. Benzoic acid and its derivatives have a wide spectrum of pharmacological activities, including antifungal activity. Therefore, the objective of this work was to prepare a collection of twenty-one derivatives of 3,5-dinitrobenzoic acid (1-21), to evaluate the antifungal activity of the compounds against strains of the genus Candida and to carry out the development and characterization of an antifungal nanoemulsion. The products were obtained through Fischer's esterification, esterification with alkyl and aryl halides, Mitsunobu reaction and reaction with acid chloride. In the structural characterization of the derivatives, infrared spectroscopic methods, 1H and 13C nuclear magnetic resonance and high resolution mass spectrometry were used. The determination of the minimum inhibitory concentration (MIC), the determination of the minimum fungicidal concentration (MFC) and the assay of determination of the mechanism of action (sorbitol and ergosterol) were carried out using the microdilution technique. The formulation was produced by ultrasound and characterized by dynamic light scattering (DLS) technique. Products were obtained in 12.46%-85.17% yields. Among the twenty-one substances obtained, one is unprecedented in the literature (9). Ester 1 showed the best antifungal profile against all Candida strains and was selected for the development of the nanoemulsion. MDNB-NE exhibited a droplet size of 181.16 ± 3.20 nm and a polydispersity index of 0.30 ± 0.03. The in vitro study showed that compound 1 and MDNB-NE inhibited the growth of all strains with minimum inhibitory concentrations of 0.27-1.10 mM. The biological results corroborate the in silico approach, which pointed to a multi-target antifungal mechanism of action for compounds 1 and 2 in C. albicans, and are in agreement with the experimental interference of 2 in the synthesis of ergosterol. Thus, the present study may serve as a basis for further research involving compounds with antifungal activity.